Effects of Structured Games Led by Classroom Teachers on Preschool Student Fundamental Motor Skills - Gita Febria Friskawati (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Early childhood is a golden period for growth and development, including Fundamental Movement Skills (FMS). However, motor learning through games is often neglected. This study was aimed to reveal the impact of playing games led directly by the class teacher on student FMS mastery. Ex post facto research was conducted on children aged 5-7 years who had received a structured game program intervention led directly by their class teacher. A total of 30 children participated in this study, consisting of 12 boys and 18 girls. This program had been incorporated into the early childhood education curriculum at the school where the research took place. FMS was measured using TGMD-2. An independent t-test was used to reveal differences of the results of FMS of the children. The results of the study showed that there were differences in the acquisition of FMS between boys and girls, where the boys gained a higher locomotor skills compared to the girls. In contrast, the mastery of manipulative skills was higher in the girl group. This study concludes that it is important to integrate structured game programs in the early childhood education environment.